(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper presents a synthesis of knowledge concerning the urban layout of Ticinum and the organization of its territory in Late Antiquity. The city, which has played a fundamental role within the Roman road network since its origins, sees a considerable increase in its strategic importance, when Milan at first and then Ravenna become imperial capitals. Through the study of discoveries around the urban center (part I) and the ager ticinensis (part II), it is possible identifying some functional areas characterizing Late Antique Pavia, both for urban space and surrounding territory.